De enredos a personagens: a articulação entre a trajetória de egressos e a formação no mestrado profissional - Müller, Vanessa (2024)
Stricto sensu postgraduate studies in the professional modality are a proposal for the qualification of workers, which aims at reflection and the quick transfer of knowledge built for professional practice, according to the demands of own society. Establishing strategies for monitoring the achievement of the objectives of this training from the perspective of graduates contributes to the qualification of the educational proposal. Establishing strategies for monitoring the achievement of the objectives of this formation from the perspective of graduates contributes to the qualification of the educational proposal. Objective: Identify the connection between training and professional trajectory based on the analysis of the narratives of graduates of a professional master's degree. Method: This is qualitative research, with a theoretical methodological approach based on the use of narrative both for data collection and for the interpretation of narrated texts, with the aim of understanding a phenomenon. The instrument for preparing the narratives was built in digital format and the collection took place online with the participants who accepted and gave their free and informed consent to use the information in this research. Results and Discussion: The narratives of the graduates revealed that their professional careers were influenced by their experiences on the master's course, with professional practice integrated with the scientific knowledge acquired during their formation, in addition to the development of critical and reflective thinking, the adoption of a new academic stance, based on the attitude of learning how to learn, with the positive influence of active methodologies in the teaching-learning process and the awakening to research. In addition, in the professional practice of the graduates, elements of management, care and education in health were reported, which are structuring axes of clinical management, with emphasis on orientation to health needs and comprehensive care; quality in health care; articulation and appreciation of different knowledge and practices in health; co-responsibility between managers, professionals and citizens in the production of health care; and development of autonomy and promotion for self-care. Final considerations: The study allowed the identification of the link between training and professional career, indicating that the approaches in the curricular activities dialog with the professional practice of the graduates, highlighting the dimensions of care, work and education in health, with emphasis on active teaching-learning methodologies.